Phosphorylation of Structural Components Promotes Dissociation of the Herpes Simplex Virus Type 1 Tegument - Morrison, Ewan E. (American Society for Microbiology, 1998)
The role of phosphorylation in the dissociation of structural components of the herpes simplex virus type 1 (HSV-1) tegument was investigated, using an in vitro assay. Addition of physiological concentrations of ATP and magnesium to wild-type virions in the presence of detergent promoted the release of VP13/14 and VP22. VP1/2 and the UL13 protein kinase were not significantly solubilized. However, using a virus with an inactivated UL13 protein, we found that the release of VP22 was severely impaired. Addition of casein kinase II (CKII) to UL13 mutant virions promoted VP22 release. Heat inactivation of virions or addition of phosphatase inhibited the release of both proteins. Incorporation of radiolabeled ATP into the assay demonstrated the phosphorylation of VP1/2, VP13/14, VP16, and VP22. Incubation of detergent-purified, heat-inactivated capsid-tegument with recombinant kinases showed VP1/2 phosphorylation by CKII, VP13/14 phosphorylation by CKII, protein kinase A (PKA), and PKC, VP16 phosphorylation by PKA, and VP22 phosphorylation by CKII and PKC. Proteolytic mapping and phosphoamino acid analysis of phosphorylated VP22 correlated with previously published work. The phosphorylation of virion-associated VP13/14, VP16, and VP22 was demonstrated in cells infected in the presence of cycloheximide. Use of equine herpesvirus 1 in the in vitro release assay resulted in the enhanced release of VP10, the homolog of HSV-1 VP13/14. These results suggest that the dissociation of major tegument proteins from alphaherpesvirus virions in infected cells may be initiated by phosphorylation events mediated by both virion-associated and cellular kinases.